ANALISE CRÍTICA DAS TENTATIVAS RECENTES DE AVALIAÇÃO DA AÇÃO EXTENSIONISTA, NA REGIÃO NORDESTE - OLIVEIRA, MAURO MÁRCIO (Cadernos de Ciência & Tecnologia, 1984)
O objetivo deste trabalho é o de formular uma análise crítica dos relatórios de avaliação dos resultados dos esforços desenvolvidos pelo Serviço de Extensão Rural, junto aos pequenos agricultores da Região Nordeste do Brasil, além de elaborar conclusões globais sobre o assunto. Para tanto foram apreciados vinte diferentes relatórios e estudos, produzidos nos últimos 10 anos. Dez deles tratam da atuação do Serviço de Extensão Rural no Polonordeste, oito no Projeto Experimental de Sergipe e dois em programas de capacitação de mão-de-obra rural. CRITICAL ANALYSIS OF THE RECENT ATTEMPTS TO EVALUATE EXTENSIONIST ACTION IN THE NORTHEAST REGION Abstract The main purpose of this paper is to summarize the results of Agricultural Extension Services within the small farmers in the Brazilian Northeast. A review of 20 technical papers related to the evaluation of such service was carried out, covering the last 10 years, beginning in 1974. Of this the studies related to special program "POLONORDESTE" account for 50% of the total; those concerned with the Experimental Project of Sergipe State account for 40% of the total and the remaining 10% are related to the behaviour of Extension Service on labor training activities.